ANALISIS LAPORAN PERTANGGUNGJAWABAN PERUSAHAAN TERHADAP STAKEHOLDERS DALAM PERSPEKTIF ISLAM (Studi Kasus Pada Bank Syariah Bukopin Dan BRI Syariah) - Rahmi Farah Diba (AKUNTABILITAS, 2015)
This study aims to analyze the compliance of Islamic banks to disclose the corporate social responsibility from Islamic perspective by using shariah enterprise theory. This study uses Bank Syariah Bukopin and BRI Syariah as the objects of the research. The data used in this study is obtained from bank’s annual report 2010-  2014 published in bank’s officialwebsite.This study shows that both of the banks have met vertical accountability to God properly. However, the disclosure of horizontal accountability to direct and indirect stakeholders as well as the nature have not fully achieved. For five years research period 2010-2014, Bank Syariah Bukopin and BRI Syariah continued to experience improvement in their corporate social responsibility report except for 2014, the year when the corporate social responsibility disclosure was not as well as the previous year.